Menerapkan Metode Klasifikasi pada Data Uji Emisi Kendaraan di Jakarta dengan Menggunakan Jupyter Notebook - Muzaky, Adamara; Arifianto, Firman; Hendrowati, Retno; Darwis, Muhammad (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
This research aims to apply classification methods using Jupyter Notebook on vehicle emission test data in Jakarta. The rapid growth of vehicles and urbanization in Jakarta has led to increased air pollution, triggering concerns among the government and city residents. This research aims to identify hidden patterns, relationships, and trends in emission test data through a Data Mining approach with classification analysis methods. It is hoped that this research will significantly contribute to understanding the characteristics of vehicle emissions in Jakarta, including identifying dominant pollutants and factors influencing vehicle emissions.